2011
DOI: 10.1093/nar/gkr033
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular sRNA transcriptome of Listeria monocytogenes during growth in macrophages

Abstract: Small non-coding RNAs (sRNAs) are widespread effectors of post-transcriptional gene regulation in bacteria. Currently extensive information exists on the sRNAs of Listeria monocytogenes expressed during growth in extracellular environments. We used deep sequencing of cDNAs obtained from fractioned RNA (<500 nt) isolated from extracellularly growing bacteria and from L. monocytogenes infected macrophages to catalog the sRNA repertoire during intracellular bacterial growth. Here, we report on the discovery of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
218
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(232 citation statements)
references
References 72 publications
4
218
0
Order By: Relevance
“…In addition, the three mutants were attenuated when assessed for growth in mouse and insect models of infection. 156 These results reveal extensive sRNA expression as an important feature of bacterial regulation during intracellular growth.…”
Section: Monocytogenesmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, the three mutants were attenuated when assessed for growth in mouse and insect models of infection. 156 These results reveal extensive sRNA expression as an important feature of bacterial regulation during intracellular growth.…”
Section: Monocytogenesmentioning
confidence: 82%
“…The discovery of 150 putative regulatory RNAs was recently reported in Listeria. 156 A total of 29 regulatory RNAs, including small non-coding antisense RNAs, are differentially expressed intracellularly. Mutants for three of these intracellularly expressed sRNA candidates revealed that their expression is required for efficient growth of bacteria in macrophages.…”
Section: Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of data shows that the Clostridia also contain sRNAs (Chen et al 2011;Mraheil et al 2011). For example, a great number and a large diversity of regulatory RNAs have been recently identified in the pathogenic clostridium Clostridium difficile (Soutourina et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first noncoding RNAs (ncRNAs) in L. monocytogenes were identified by coimmunoprecipitation with Hfq, a small RNA-binding protein required for the activity of small regulatory RNAs in prokaryotes [21] and by an in silico-based approaches [22]. Since then, the use of high-density tiling arrays and RNA deep sequencing provided a picture of the whole L. monocytogenes transcriptome in multiple conditions, allowing the discovery of many regulatory RNAs [23][24][25][26][27][28] and the annotation of hundreds of regulatory RNAs in L.…”
Section: Unconventional Mechanisms Regulating Bacterial Gene Expressimentioning
confidence: 99%